2011
DOI: 10.1016/j.ymgme.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACACB polymorphisms with obesity and diabetes

Abstract: Acetyl-CoA carboxylase beta, encoded by the ACAB gene, plays an important role in the oxidation of fatty acids. The aim of this study was to check the hypothesis that allelic variants of ACACB influence the risk of obesity and type 2 diabetes mellitus. Twenty five tagging single nucleotide polymorphisms (SNPs) capturing common variants of the ACACB gene were selected and analyzed in two cohorts including 1695 postmenopausal women of the general population and in 161 women with severe obesity (BMI>35). In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
(17 reference statements)
1
39
0
Order By: Relevance
“…ACACB, one isoform of ACAC, is involved in fatty acid oxidation (36,37). The variants of the ACACB allele are associated with obesity (38). A previous study showed that body fat may act as a mechanism of metabolic adaptation and a signal that downregulated ACACB expression in adipose tissue (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACACB, one isoform of ACAC, is involved in fatty acid oxidation (36,37). The variants of the ACACB allele are associated with obesity (38). A previous study showed that body fat may act as a mechanism of metabolic adaptation and a signal that downregulated ACACB expression in adipose tissue (39).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that body fat may act as a mechanism of metabolic adaptation and a signal that downregulated ACACB expression in adipose tissue (39). In addition, rs2268388 polymorphisms of ACACB are associated with severe obesity and ACACB has a significant part in disorders associated with energy metabolism such as obesity (38). Furthermore, ACACB is involved in triglyceride synthesis and triglyceride contents of soleus muscle were greater in obese than in lean individuals (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…At the juncture of lipid synthesis and oxidation pathways, inhibition of this enzyme presents a therapeutic target for metabolic syndrome. ACACB polymorphisms are associated with obesity, diabetes and metabolic syndrome in humans52. The gain in 12q24.11 ( ACACB ) was described in the DGV.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of nuclear extracts from sub-confluent HepG2 cell cultures and Electrophoretic Mobility Shift Assays (EMSAs) were done as reported by Riancho et al [26]. The gel bands were analyzed in an ODYSSEY infrared imaging system (Li-Cor Biosciences, Lincoln, NE).…”
Section: Methodsmentioning
confidence: 99%